The Effectiveness of Differentiated Learning on Critical Thinking Skills and Student Activeness in Mathematics Learning - Suparni Suparni; Rahayu Condro Murti (STAI Hubbulwathan Duri, 2025)
This study aimed to examine the effectiveness of differentiated learning in enhancing critical thinking skills and student activeness in mathematics among fourth-grade students in public elementary schools in the Trucuk District, Klaten. Differentiated learning is designed to address diverse student needs, interests, and abilities through tailored content, process, and assessment strategies. A quasi-experimental design was employed, involving 70 students from four randomly selected schools. Two schools were assigned as experimental groups implementing differentiated learning, while the remaining two served as control groups using conventional teaching methods. Data were collected through critical thinking tests and observation sheets measuring student activeness. Statistical analyses included descriptive statistics, classical assumption tests, and hypothesis testing using paired t-tests. The findings revealed a statistically significant difference between the experimental and control groups. Students in the experimental group demonstrated higher critical thinking scores (mean = 54.20) than those in the control group (mean = 42.83), with a t-value of 17.717 and a p-value of 0.000 (p 0.05). Similarly, student activeness improved significantly in the experimental group (mean = 53.34) compared to the control group (mean = 43.51), supported by a t-value of 6.254 and a p-value of 0.000. The results suggest that differentiated learning effectively enhances both critical thinking and student activeness in mathematics. Individualized instruction provides meaningful engagement and supports cognitive development, particularly in elementary education. This study highlights the importance of responsive teaching strategies in fostering student-centered learning environments.